The protective effects of myricetin against acute liver failure via inhibiting inflammation and regulating oxidative stress via Nrf2 signaling. Issue 5 (4th March 2023) - Wang, Xia; Sun, Youpeng; Li, Peixuan; Wu, Zhikai; Chen, Yichun; Fu, Yiwu; Wu, Hanpeng; Ye, Yingrong; Wang, Jingjing; Yang, Zhengtao; Zhou, Ershun
Abstract: This study aimed to investigate the protective effects and mechanisms of myricetin on acute liver failure in mice induced by lipopolysaccharide (LPS)/D-galactosamine (D-Gal). Our results showed myricetin (25, 50 and 100 mg/kg) pretreatment significantly improved the pathological changes of liver tissues, decreased serum ALT and AST (p < 0.001) induced by LPS/D-GalN. Moreover, MDA and MPO levels were reduced (p < 0.001), CAT and SOD activities were increased (p < 0.001) with myricetin (50 and 100 mg/kg) pretreatment. Likewise, inflammatory cytokines TNF-α and IL-6 mRNA in liver tissues were markedly decreased (p < 0.001) by myricetin. Besides, Nrf2 protein expression was drastically elevated (p < 0.001) by myricetin (25, 50 and 100 mg/kg). All these findings imply that myricetin may protect against acute liver failure by suppressing inflammation and regulating oxidative stress via Nrf2 signaling, and that it may be a possible strategy to avoid liver damage. Graphical Abstract: UF0001